Electron Transfer At Metal/Molecule Interface - Al-Agealy, Hadi J. M.; Fadhil, Mohammed Z. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Theoretically description of the electron transfer of the electron transfer of met/mol has been investigated in this work according to the quantum theory. By using a model that is derived depending on the first order perturbation theory, the rate constant at met/mol interface can be calculated with the calculated reorganization energy. The reorganization energy that is evaluated according to the outer sphere model is based on the electstatistics potential of the molecular donor and acceptor. The molecular parameters introduced in this model are the molecular weight, mass, density, and radius of molecule have been evaluated according to the apparent molar volume using spherical approach.       The theoretical results are obtained according to our model of rate constant for electron transfer, a corresponding with the experimental data for some qualilative metal/molecule interface some qualitative of the experimental studies .